ANALYSIS OF FACTORS AFFECTING DEBT POLICY - Suci Meta Saputri; Widi Hariyanti; Yunus Harjito (Universitas Airlangga, 2020)
This study aims to analyze the effect of profitability, liquidity, asset structure and company growth on debt policy. The sample in this study amounted to 490 samples obtained from 98 companies for 5 years with purposive sampling method. The data analysis technique used in this research is panel data regression analysis technique which is processed using Eviews 9 software.The results show that profitability and liquidity have a negative effect on debt policy, while asset structure has no effect on debt policy, and company growth has a positive effect on debt policy. debt policy.